Thomas & friends. Thomas' Halloween adventures - Allcroft, Britt; Awdry, W.; Anchor Bay Entertainment, Inc. (Troy, MI : Distributed by Anchor Bay Entertainment, 2006)
Are there really ghosts in the fog and mist on the Island of Sodor? Thomas, Toby and Henry believe that there are. But things are not always as they appear. Gordon and Percy encounter other mysteries on the Island. Can Thomas help explain them?
Scaredy engines -- Haunted Henry -- Thomas gets tricked -- Thomas, Percy & the dragon -- Diesel's devious deed -- Percy's ghostly trick -- Toby's discovery -- Gordon and the gremlin -- The fogman -- Bad day at Castle Loch -- Percy and the haunted mine.
Created by Britt Allcroft ; Based on "The railway series" by The Reverend W. Audry.
Bonus features: Character gallery; Read-along story "The great race"; 2 sing-along-songs: "Boo! boo! Choo-choo!" and "Engine roll call"; Bonus DVD game: "Learn to count".
Not rated.
DVD, region 1; Dolby Digital.
Closed-captioned.
Keywords: Thomas the Tank Engine (Fictitious character) -- Juvenile drama; Halloween -- Juvenile drama; Television programs for children; Video recordings for the hearing impaired; Animated television programs